Respostas

2013-12-16T15:18:11-02:00
X + y + z  = 10 
-x+y+z = 3
2x + y +z = 0  

x = 10 - y - z
-10+y+z+y+z =3 
2x + y + z = 0 

---------------
-13 = -2y - 2z 
--------------

-----------
(-13 + 2y)/-2 = z
2(10 - y - z) + y + z = 0 

........
.........
20 - 2y - 2z + y +z = 0 

................
..............
20 - y - (-13 + 2y)/-2 = 0 


C.AUXILIAR:
-y = - 20 - ((-13 + 2y)/-2)  <=>
<=> -y = -20 - ((13/2 + -y) <=>
<=> -y = - 20 - 13/2 + y <=>
<=> -2y = - 20 - 13/2 <=>
<=> -2y = 27/2<=>
<=>-y = 27 <=>
<=> y = -27

Regressando ao nosso belo sistema:
............................
(-13 + 2y)/-2 = z
y = -27 

Cálculo auxiliar:
(-13 + 2y)/-2 = z <=>
<=> 13/2 - y = z <=>
<=> 13/2 - (-27) = z <=>
<=> z = 67/2

Regressando ao sistema:
x = 10 - y - z
z = 67/2
y = -27

x = 10 - (-27) - 67/2 = 7/2
z = 67/2
y = -27 

Verificação:
x + y +z =10 
 7/2 + (-27) + 67/2 = 10 (VERDADEIRO)

-x +y + z = 3
-7/2 + (-27) + 67/2 = 3 (Verdadeiro)

2x+y+z=0
2 (7/2) + (-27) + 67/2 = 0 Verdadeira